Factors Associated with Antibiotic Prescribing in Children with Otitis Media. (26th February 2013) - Ryborg, Christina T.; Søndergaard, Jens; Lous, Jørgen; Munck, Anders; Larsen, Pia V.; Hansen, Malene Plejdrup; Thomsen, Janus Laust
Abstract : Background . Acute otitis media (AOM) is often treated with antibiotics. However, initial observation is recommended. Denmark has a low use of antibiotics compared with other countries, but the total use of antibiotics has increased by 32% during the last decade, and it is important to know whether general practitioners (GPs) prescribe antibiotics according to guidelines. Objective . The aim of the study was to analyse associations between GPs' antibiotic prescribing for AOM and symptoms, diagnoses, and characteristics of children. Methods . A cohort study where GPs consecutively included 954 children between 0 and 7 years old with a new ear symptom was carried out. The GPs registered symptoms, results of otoscopy and tympanometry, together with diagnosis and treatment. Results . Fever with and without earache was statistically associated with prescribing antibiotics, and it applies to both children up to two years of age (OR: 5.89 (confidence interval (CI): 2.62–13.21) and OR: 8.13 (CI: 4.61–14.32)) and children older than two years of age (OR: 4.59 (CI: 2.55–8.25) and OR: 19.45 (CI: 6.38–59.24)). A red tympanic membrane was statistically associated with the prescribing antibiotics in both age groups (0–2 years: OR: 4.73 (CI: 2.52–8.86) and >2–7 years: OR: 3.76 (CI: 2.13–6.64)). A flat tympanometry curve was only statistically associated with prescribing antibiotics in the oldest children (OR: 2.42 (CI: 1.17–5.00)). Conclusion . This study indicates that GPs to a large degree prescribe antibiotics appropriately according to guidelines.